Comparative efficacy of different exercise types on body composition in university students: a systematic review and meta-analysis of randomized controlled trials - Li, Jihai; Zang, Liuhong; Hao, Sihai; Wang, Hui (Frontiers in Physiology, 2025)
BackgroundTo systematically assess the impact of various exercise modalities and dosages on the body composition of college students through a comprehensive review of randomized controlled trials (RCTs).MethodsWe conducted a comprehensive search of relevant randomized controlled trials (RCTs) in eight databases, covering data from the inception of each database to August 2024. Following the literature screening, two investigators independently conducted data extraction and assessed the risk of bias. Network meta-analysis (NMA) was conducted using Stata 17.0 with random-effects modeling, while dose-response analysis was performed utilizing R version 4.3.1.ResultsA total of 43 randomized controlled trials (RCTs), encompassing 3,154 participants, were included in the analysis. Aerobic exercise, combined exercise, high-intensity interval training (HIIT), mind-body exercise, and calisthenics demonstrated significant effects on reducing body mass index (BMI) compared to control groups. Surface under the cumulative ranking (SUCRA) probability rankings indicated that calisthenics had the highest likelihood of being the most effective intervention for BMI reduction, whereas resistance exercise was associated with the lowest likelihood. The dose-response analysis revealed that the threshold exercise dose for overall exercise to lower BMI was 310 METs-min/week, with the predicted maximum significant response dose being 1,300 METs-min/week, beyond which there was minimal change in the intervention effect. Additionally, distinct nonlinear dose-response relationships were observed for aerobic exercise, combined exercise, HIIT, mind-body exercise, and aerobics.ConclusionNo significant differences in the effectiveness of exercise interventions on body composition were observed across exercise types. However, based on the SUCRA analysis, calisthenics emerged as the preferred intervention, succeeded by a combination of exercises. The optimal exercise dosage for enhancing body composition was identified as 1,300 METs-min/week, with the threshold for a significant effect being relatively low.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024587032